(untitled) (Indian Journal of Animal Production and Management, 2017)
The present study was conducted in the Surat district of Gujarat. Total 300 respondents were interviewed for the questionnaire prepared about improved dairy husbandry practices adopted by them and constraints in adoption of those practices. The findings indicated that majority of dairy farmers had medium adoption level on different component of improved dairy husbandry practices viz. 62.33% for housing, 65.33% for feeding, 57% for breeding, 62.34% for healthcare, 68.33% for milking management and 70% for calf rearing. The overall adoption levels of the respondents in improved dairy husbandry practices fall under low, medium and high categories are 9.33%, 75.34% and 15.33%, respectively. The adoption index of different aspect of improved dairy husbandry practices of housing, feeding, breeding, health care, milking and calf rearing were 44.97, 40.90, 64.98, 51.55, 50.60 and 50.85%, respectively and overall adoption index of improved dairy husbandry practices was 50.64% which indicated medium adoption level of dairy farmers in the study area. The majority of dairy farmers had high construction cost (94%), lack of own capital (64%), high cost of feed (97.33%), non-availability of green fodder round the year (85.33%), lack of awareness about treatment of poor quality straw to improve its nutritive value (68.67%), repeat breeding problems in dairy animals (88.67 %), non-remunerative price for milk (93.67%), lack of knowledge in clean milk production (71.33%), high cost of veterinary medicine (78.67%), problem of mastitis in dairy animals (71.33%) and inadequate knowledge of diseases and their control (67.33%) were major constraints in adoption of improved dairy husbandry practices.